Hemimandibulectomy With Mandibular Reconstruction as Management of Odontoma Complex; Case Report - Dastia, Vanda Chrisina; Salsabila, Nadia; Rachmawati, Dini; Utami, Devi Farida; Pahlevi, Muhammad Reza (Jurnal Sehat Indonesia (JUSINDO), 2025)
Introduction: Odontomas are the most common of the odontogenic tumours in the jaws and are characterized by their slow growth, asymptomatically, non-aggressively, and reaching no more than 3cm in diameter. Odontomas generally consist of unerupted or impacted teeth and retained deciduous teeth. This case report presents a rare case of complex with a large-size odontoma, measuring more than 3 cm in diameter, in the left posterior of the mandible along with impacted teeth. The lesion was removed with a hemi mandibulectomy. Case Report: A 24-year-old woman came with the chief complaint of a mass in the left lower jaw for 3 years. On clinical examination, a mass appeared in the left mandibular edentulous ridge with firm boundaries and a solid consistency, with no palpable Christ or crepitation. Incisional biopsy was performed, and the diagnosis showed it was fibrous dysplasia. Treatment was carried out with a left hemi mandibulectomy and reconstruction with a plate under general anaesthesia. The tumour defect was sent for anatomical pathology examination and the results showed the impression of a complex odontoma. Discussion: Odontomas are the most common odontogenic tumors and are classified into benign, mixed, and calcifying odontogenic tumors. Odontomas are generally found between the ages of 1 and 30 years, with the incidence occurring more frequently in women. These lesions occur more frequently in the lower jaw than the upper jaw. In this case, the patient is a 24 years old female. Although the cause is not yet known for certain, possible causes of odontoma may include traumatic injury to primary teeth, hereditary factors, and genetic disorders. In this case report, the odontoma was large and the extensive lesion had caused damage to the surrounding structures. Because the mass of the lesion was large and widespread, a radical hemi mandibulectomy was performed on the left mandibular region. Concussion: Odontomas are odontogenic tumors that most often occur in the jaw and can be found by dentists during routine examinations accompanied by panoramic radiography. Although odontoma is asymptomatic and has limited growth, potency, early diagnosis, and surgical excision are necessary to avoid complications such as cystic changes and malocclusion due to displacement of adjacent permanent teeth